2020
DOI: 10.1063/5.0025124
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic skyrmionium diode with a magnetic anisotropy voltage gating

Abstract: The magnetic skyrmionium can be seen as a coalition of two magnetic skyrmions with opposite topological charges and has potential applications in next-generation spintronic devices. Here, we report the current-driven dynamics of a skyrmionium in a ferromagnetic nanotrack with the voltage-controlled magnetic anisotropy. The pinning and depinning of a skyrmionium controlled by the voltage gate are investigated. The current-driven skyrmionium can be used to mimic the skyrmionium diode effect in the nanotrack with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…1,2 Owing to the unidirectional operation of the electrical diode, considerable interest has been generated in various physical disciplines, including acoustics, 3 microuidics, 4 photonics, 5 thermodynamics, 6 and micromagnetism. 7 Magnetic skyrmions, a nonlinear nanoscale spin texture, found in chiral magnets with broken inversion symmetry, can be viewed as viable information carriers due to their particle-like nature benetting from unidirectional transport for diode applications. 8,9 The unique properties of skyrmions, such as topological stability, nanoscale size, and ultra-low driving current density, make them ideal candidates for spintronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Owing to the unidirectional operation of the electrical diode, considerable interest has been generated in various physical disciplines, including acoustics, 3 microuidics, 4 photonics, 5 thermodynamics, 6 and micromagnetism. 7 Magnetic skyrmions, a nonlinear nanoscale spin texture, found in chiral magnets with broken inversion symmetry, can be viewed as viable information carriers due to their particle-like nature benetting from unidirectional transport for diode applications. 8,9 The unique properties of skyrmions, such as topological stability, nanoscale size, and ultra-low driving current density, make them ideal candidates for spintronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[44,45]. Several works have demonstrated that the zero net topological charge of a skyrmionium allows its motion along the driving current without transverse drift [44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmion domains can become punctured, thereby leading to the formation of concentric skyrmions with opposite topological charges upon unloading of the pressure. The combination of the two oppositely charged skyrmions form a topological composite called skyrmionium, which has been investigated in magnetic materials for next generation spintronics based devices , but not in ferroelectric materials. To the best of our knowledge, this is the first demonstration of skyrmion-to-skyrmionium “reaction” in ferroelectric materials.…”
mentioning
confidence: 99%